2019
DOI: 10.2196/15048
|View full text |Cite
|
Sign up to set email alerts
|

A Test of Feasibility and Acceptability of Online Mindfulness-Based Stress Reduction for Lesbian, Gay, and Bisexual Women and Men at Risk for High Stress: Pilot Study

Abstract: Background In conservative and rural areas, where antidiscrimination laws do not exist, lesbian, gay, and bisexual (LGB) people are at risk for excess stress arising from discrimination. Stress-reducing interventions delivered via innovative channels to overcome access barriers are needed. Objective This study aimed to investigate the feasibility and acceptability of online mindfulness-based stress reduction (OMBSR) with LGB people in Appalachian Tennes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Facilitating emotion regulation using therapeutic interventions such as mindful awareness, cognitive restructuring, and assertiveness training has shown promise in helping sexual minority men cope more effectively with minority stress (Burton et al, 2019) and may also be helpful to sexual minority women and gender minorities. For example, a pilot study of an 8-week online mindfulness-based stress reduction was found to reduce vigilance in sexual minority women by 21% (Jabson Tree & Patterson, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Facilitating emotion regulation using therapeutic interventions such as mindful awareness, cognitive restructuring, and assertiveness training has shown promise in helping sexual minority men cope more effectively with minority stress (Burton et al, 2019) and may also be helpful to sexual minority women and gender minorities. For example, a pilot study of an 8-week online mindfulness-based stress reduction was found to reduce vigilance in sexual minority women by 21% (Jabson Tree & Patterson, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies (e.g., Gonzalez et al, 2018; Jabson Tree & Patterson, 2019; Kranz & Pierrard, 2018) have used the Daily Heterosexist Experiences Questionnaire (Balsam et al, 2013), which includes a vigilance subscale; however, five of the six items assess concealment and hiding behaviors rather than hypervigilance. The Gender Identity Reflection and Rumination Scale (Bauerband & Galupo, 2014) assesses an internal process in reaction to perceived threats in the environment that differs from pervasive and chronic alertness to potential danger or threat.…”
Section: Hypervigilance In Lgbtq Individualsmentioning
confidence: 99%
“…Felner et al, 2020). Mindfulnessbased interventions were found to effectively reduce depression, avoidance, the impact of traumatic events, and minority-related stress (Tree and Patterson, 2019).…”
Section: Mindfulness In Therapymentioning
confidence: 99%
“…Mindfulness meditation is a practice that focuses on an individual’s attention on the present moment, leading to reduced levels of stress [ 11 ]. Web-based mindfulness interventions among SGMs have been associated with lower levels of perceived stress compared with baseline readings in both men and women, as well as reduced sexual minority stress in SGM women [ 12 ]. Mindfulness interventions can also lead to increased individual resilience toward discriminatory experiences [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The participants will be randomized to at least one of the 3 intervention components of awareness, connection, and purpose for this optimization study, which comprises the 8 conditions. Each of these components is known to be effective in reducing stress and promoting well-being among populations that experience high rates of discrimination (eg, SGMs) [ 12 - 14 ]. These components will be administered via the Healthy Minds Program (HMP) app with the goal of examining which combination of components most effectively reduces stress from discrimination among racial or ethnic SGMs.…”
Section: Introductionmentioning
confidence: 99%